Sleep Disturbances and Obstructive Sleep Apnea in Children and Adolescents with Cerebral Palsy: An Observational Study - Meneses da Silva, Isabella; do Couto, Maria Clara Helena; da Silveira Cruz-Machado, Sanseray; de Andrade, Leticia Monteiro; Marques, Ana Elisa Zuliani Stroppa; Giacheti, Celia Maria; Pedroni, Cristiane Rodrigues; Pinato, Luciana (Neurology international, 2025)
Background/Objectives: Cerebral palsy (CP) is a neurodevelopmental disorder associated with sleep disturbances, particularly sleep-disordered breathing (SDB), and is often linked to an increased risk of obstructive sleep apnea (OSA). OSA is underdiagnosed in this population due to the lack of standardized methods and limited access to appropriate diagnostic technologies and appropriate equipment. Thus, this study aimed to investigate the presence and severity of sleep disorders, with a particular focus on OSA, in children and adolescents with CP compared to their typically developing peers. Methods: This observational, clinical, and prospective study included 28 children and adolescents with CP and 32 age- and sex-matched typically developing individuals. Sleep disturbances were assessed using the Sleep Disturbance Scale for Children (SDSC) and a high-resolution oximeter plus actigraphy combined with a cloud-based algorithm for the detection of obstructive sleep apnea (Biologix® system), which provided data on oxygen saturation, snoring, movement during sleep, and total sleep time. Results: According to the SDSC, 92% of children and adolescents with CP presented scores indicative of sleep disturbances, compared to 31% of typically developing individuals. SDB was the most prevalent subtype (64%) and overnight oximetry revealed that 100% of the CP group presented oxygen desaturation index (ODI) values consistent with a diagnosis of OSA. The CP group also exhibited significantly lower mean SpO2, longer snoring duration, shorter total sleep time, and prolonged sleep latency compared to the typically developing group. Conclusions: Children and adolescents with cerebral palsy (CP) exhibit a high prevalence of sleep disturbances, with increasing evidence indicating a significant occurrence of sleep-disordered breathing (SDB), particularly obstructive sleep apnea (OSA).